'Call the Norwegian embassy!': The Alta conflict, Indigenous narrative and political change in the activist films The Taking of Sámiland and Let the River Live. Issue 1 (1st March 2022) - Sand, Stine Agnete
In the 1970s, Norway had not officially acknowledged their Indigenous population, the Sámi. In the following decade, two activist films, Let the River Live (Greve 1980) and The Taking of Sámiland (Eriksen and Tannvik 1984), focused on the Alta conflict ‐ protests against the construction of a power plant in Sámi territory ‐ Indigenous rights and colonial processes. Inspired by discussions concerning documentary, activism and decolonialism, this article investigates how the films frame Sámi interests and challenge perceptions of the Norwegian state. Because both films are collaborations across ethnic boundaries, they also challenge the supposed insider/outsider perspective of Sámi and Indigenous film, offering decolonial narratives by centring on Indigenous voices and experiences, confronting the idea of Norway as homogenous and representing the state as a colonial oppressor. They represent a political turning point that has changed politics, film production and collective memory.